Does age protect against loss of tonotopy after acute deafness in adulthood? - Rosskothen-Kuhl, Nicole; Green, Sarah; Jakob, Till F. (Frontiers in Cellular Neuroscience, 2024)
The mammalian auditory system develops a topographical representation of sound frequencies along its pathways, also called tonotopy. In contrast, sensory deprivation during early development results in no or only rudimentary tonotopic organization. This study addresses two questions: (1) How robust is the central tonotopy when hearing fails in adulthood? (2) What role does age play at time of deafness? To address these questions, we deafened young and old adult rats with previously normal hearing. One month after deafening, both groups were unilaterally supplied with cochlear implants and electrically stimulated for 2 h. The central auditory neurons, which were activated as a result of the local electrical intracochlear stimulation, were visualized using Fos staining. While the auditory system of young rats lost the tonotopic organization throughout the brainstem, the auditory system of the older rats mainly sustained its tonotopy. It can be proposed that plasticity prevails in the central auditory system of young adult rats, while network stability prevails in the brains of aging rats. Consequently, age may be an important factor in protecting a hearing-experienced adult auditory system from a rapid loss of tonotopy when suffering from acute hearing loss. Furthermore, the study provides compelling evidence that acute deafness in young adult patients should be diagnosed as early as possible to prevent maladaptation of the central auditory system and thus achieve the optimal hearing outcome with a hearing prosthesis.